2013
DOI: 10.1603/ec13100
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Evaluation of Two Transgenic Maize Events Expressing Fused Proteins to Cry1Ab-Susceptible and -Resistant <I>Ostrinia furnacalis</I> (Lepidoptera: Crambidae)

Abstract: The Asian corn borer, Ostrinia furnacalis (GuenCe), is a major pest of maize in China. Transgenic Bt maize could provide an effective way to control this pest. However, the potential of resistance evolution has been documented in the laboratory-a CrylAb-resistant strain of Asian corn borer (Asian corn borer-AbR) could survive well on two Bt maize events, that is, MON810 and Bt11. Pyramided transgenic crops with multiple dissimilar Bt insecticidal proteins offer a superior route for pests control compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…To date, China has obtained many Bt maize lines, all of which express cry1 and/or cry2 genes targeting lepidopteran pests [4,5,6,7]. Most of the Bt maize lines, such as IE09S034 (expressing a cry1Ie gene), BT-799 (expressing a modified mcry1Ac gene), and Shuangkang12-5 (expressing a fusion cry1Ab/2Aj gene) have proven to be effective against lepidopteran pests [8,9]. In the case of Bt maize expressing cry1Ie , the Chinese Ministry of Agriculture has already approved field trials for assessing the environmental risks, indicating its potential to be commercialized in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…To date, China has obtained many Bt maize lines, all of which express cry1 and/or cry2 genes targeting lepidopteran pests [4,5,6,7]. Most of the Bt maize lines, such as IE09S034 (expressing a cry1Ie gene), BT-799 (expressing a modified mcry1Ac gene), and Shuangkang12-5 (expressing a fusion cry1Ab/2Aj gene) have proven to be effective against lepidopteran pests [8,9]. In the case of Bt maize expressing cry1Ie , the Chinese Ministry of Agriculture has already approved field trials for assessing the environmental risks, indicating its potential to be commercialized in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in China showed that Cry1Ab-expressing maize MON810 and Bt11 could effectively protect against the Asian corn borer and other lepidopteron pests [17,18,19,20]. However, the potential of resistance evolution has been documented in the laboratory resulting in Cry1Ab-resistant colonies of ACB with the propensity to survive well on two Bt maize events [21]. Under laboratory conditions and using artificial diets containing Cry1Ab protein, resistance of O. furnacalis towards the Bt toxin increased more than 100-fold after 35 generations [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent increases in Bt corn adoption are attributed to newly released Bt hybrids with pyramided genes that effectively suppress a wider range of lepidopteran pests and stacked genes for corn rootworm (CRW, including northern corn rootworm, Diabrotica barberi , and western corn rootworm, Diabrotica virgifera virgifera ) (Buntin, 2008; Hoffmann et al, 2014). All Bt hybrids effectively control the ECB, but different Bt events and gene combinations vary widely in their efficacy against other caterpillar pests (Chang et al,2013; Frank et al, 2013; Rule et al, 2014). The cost of Bt corn seed has increased significantly in recent years compared with when it was initially released, especially with the introduction of multiple‐trait hybrids (Fernandez‐Cornejo et al, 2014; National Research Council, 2010).…”
mentioning
confidence: 99%